2012
DOI: 10.1039/c2jm33692h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the selectivity and sensitivity of mesoporous dielectric multilayers by modifiying the hydrophobic–hydrophilic balance of the silica layer

Abstract: We investigate the possibility of tuning the selectivity and sensitivity of SiO 2 /TiO 2 mesoporous dielectric multilayers for the adsorption of analytes with different chemical polarities. The hydrophilichydrophobic balance of the mesoporous SiO 2 layer was controlled by one-pot co-condensation of mixtures of methyltriethoxysilane (MTES) and tetraethyl orthosilicate (TEOS) in variable contents. Infrared spectroscopy analysis combined with water contact angle measurement confirmed the gradual increase of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…PCs designed from 1D, 2D, and 3D periodical arrangement of materials interact with electromagnetic radiation and inhibit the propagation of light in well-defined wavelength (energy) ranges and directions (photonic band gap) (Figure 11b). Many developments in waveguides [56], dielectric mirrors, sensors [57], and low threshold lasers [58] derive directly from the photonic band gap property. However, the propagation of light at the bandgap edges recently attracted attention in photocatalytic applications.…”
Section: D Nanostructure An Accelerator Of the Photochemistrymentioning
confidence: 99%
“…PCs designed from 1D, 2D, and 3D periodical arrangement of materials interact with electromagnetic radiation and inhibit the propagation of light in well-defined wavelength (energy) ranges and directions (photonic band gap) (Figure 11b). Many developments in waveguides [56], dielectric mirrors, sensors [57], and low threshold lasers [58] derive directly from the photonic band gap property. However, the propagation of light at the bandgap edges recently attracted attention in photocatalytic applications.…”
Section: D Nanostructure An Accelerator Of the Photochemistrymentioning
confidence: 99%
“…The surface properties of hybrid sol-gel material can considerably affect their analytical performance [17]. For example, it has been shown that the modification of the hydrophobic-hydrophilic balance of the hybrid silica layer can be used to tune the selectivity and sensitivity [18]. Numerous studies on ion-imprinted polymers and their application for selective pre-concentration and separation of Hg 2?…”
Section: Introductionmentioning
confidence: 99%
“…In particular, 3D artificial photonic crystals are considered as one of the most potential materials due to their permittivity modulation along all three directions. Furthermore, their complete photonic band-gap could reflect electromagnetic waves in all directions [24,25]. It is well-recognized that photonic nanostructures improve the Bragg scattering in the material and have the ability to reduce the group velocity of photons [26].…”
Section: Introductionmentioning
confidence: 99%